The Evaluation Of Nutrition Containers In Hope Of New Type Of Red Rice Cross Silopuk Cultivar Using Fatmawati Variety - Etti Swasti (Department of Crop Science, Faculty of Agriculture, Andalas University, 2020)
Absrtrak Entering moderniasi era, awareness of the public about the importance of health and healthy lifestyle has begun to be applied, one consuming rice are high in protein and low in carbohydrates such as brown rice. This study aims to determine the nutritional content of the lines of hope crossing Silopuk cultivars with superior varieties Fatmawati . The research took place from September to October 2019. The genetic material used was the F5 generation seed selected from 18 families and selected as many as 6 families to be tested for protein content, food fiber, carbohydrates and glycemic index. . The results showed a protein content ranging from 12 , 24 % to 17.56%. The value of the protein content was lowest for the strain SF5-118-35-15 that is the biggest 12 , 24 %, while the value of the highest protein content found in different types of rice SF5-12-26-4 that is equal to 17.56%. The level of food fiber ranges from 1 , 05 % to 4.31%. The highest value of food fiber content is in the SF5-12-48-17 strain which is equal to 4 , 31 % and the lowest food fiber content is in the SF5-118-35-15 strain which is 1.05%. Carbohydrate content ranges from 66 , 5122 % to 71.9867%. The highest carbohydrate content is in the SF5-118-35-15 strain which is 71.9867% and the lowest is in the SF5-12-26-4 strain which is 66.5122%. The glycemic index ranging from 46 , 56 % to 54.98% and relatively low criteria. Keywords : Carbohydates, family, food fiber , glycemic index , protein